2018
DOI: 10.1186/s12890-018-0680-y
|View full text |Cite
|
Sign up to set email alerts
|

NOX4 expression and distal arteriolar remodeling correlate with pulmonary hypertension in COPD

Abstract: BackgroundPulmonary hypertension (PH) in chronic obstructive pulmonary disease (COPD) is suggested as the consequence of emphysematous destruction of vascular bed and hypoxia of pulmonary microenvironment, mechanisms underpinning its pathogenesis however remain elusive. The dysregulated expression of nicotinamide adenine dinucleotide phosphate (NADPH)-oxidases and superoxide generation by pulmonary vasculatures have significant implications in the hypoxia-induced PH.MethodsIn this study, the involvement of NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
(68 reference statements)
0
24
0
Order By: Relevance
“…Although biochemical evidence suggests H 2 O 2 is the major product of NOX4 [ 99 , 100 , 101 ], NOX4-dependent generation of both O 2 .− [ 82 , 97 ] and H 2 O 2 [ 82 , 95 , 96 ] has been observed in the pulmonary vasculature. NOX4 expression in PAs from COPD patients [ 102 ] and CH mice [ 90 ] is higher than those from controls. NOX4 promotes proliferation of human PASMCs [ 90 ] and correlates with the severity of PA remodeling in COPD patients [ 102 ], suggesting a pathological role for NOX4 in CH-induced PH.…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Although biochemical evidence suggests H 2 O 2 is the major product of NOX4 [ 99 , 100 , 101 ], NOX4-dependent generation of both O 2 .− [ 82 , 97 ] and H 2 O 2 [ 82 , 95 , 96 ] has been observed in the pulmonary vasculature. NOX4 expression in PAs from COPD patients [ 102 ] and CH mice [ 90 ] is higher than those from controls. NOX4 promotes proliferation of human PASMCs [ 90 ] and correlates with the severity of PA remodeling in COPD patients [ 102 ], suggesting a pathological role for NOX4 in CH-induced PH.…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…NOX4 expression in PAs from COPD patients [ 102 ] and CH mice [ 90 ] is higher than those from controls. NOX4 promotes proliferation of human PASMCs [ 90 ] and correlates with the severity of PA remodeling in COPD patients [ 102 ], suggesting a pathological role for NOX4 in CH-induced PH. In comparison to wild-type (WT) mice, Hood et al [ 98 ] demonstrated that RVSP is diminished in NOX4 knockout (KO) mice following CH (10% O 2 for 15 days).…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…While all seven NOX enzymes are all expressed in various cell types within the lung, relatively little is known with respect to their potential role in COPD pathology. Several reports indicate that NOX4 is upregulated in airway smooth muscle of COPD patients and correlates with disease severity (17,18). NOX2, primarily expressed in cells of the innate immune system, also appears to be increased in COPD, and some studies suggest that NOX2 contributes to experimental emphysema, although contrasting findings were reported as well and NOX2-deficiency may even promote spontaneous emphysema (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…and DUOX2 with airflow obstruction; NOX1 with airway inflammation (neutrophils and eosinophils) [306]. NOX4 may also be involved in promoting airway smooth muscle remodelling in the small airways of COPD [311,312] and is readily induced by cigarette smoke [307]. Thus, isoform differences may impact effectiveness of new therapies targeting NOXgenerated ROS, particularly as drugs like apocynin are isoform-specific [308].…”
Section: Oxidative Stressmentioning
confidence: 99%